Changes in financial structure and industry product markets: An econometric analysis - Antonio Zotti (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper presents a micro-econometric model testing for changes in firms' product and pricing decisions in two American industries where leading companies have sharply increased their financial leverage. According to the latest econometric theory, the empirical analysis is carried out through an error-correction model (ECM) which allows to separate the long-term from the short-term relationship between variables. The results from estimating show that the average industry debt ratio is a significant variable in determining product price level. In the first industry there is a positive correlation between debt and output; in the second industry output is negatively associated with the average industry debt ratio. Findings from the empirical analysis not only show the significance of debt's proportion in firms' financial structure, but also point out the importance of linking different effects of debt to specific scenarios (rivals' low financial leverage, low entry barriers, etc.).
Keywords: C32; C51; G32; L13; L7; 330; Kapitalstruktur; Industrieprodukt; Theorie